Critical Review of the O.O.Tieliezhkina's Monograph “SOUND-WORD-TEXT: the Language of the Ukrainian Poetry of the Second Half of the XX – Early XXI Century (Linguostylistic Studies, 2020)
CRITICAL REVIEW OF THE O.O.Tieliezhkina's Monograph “SOUND-WORD-TEXT: the Language of the Ukrainian Poetry of the Second Half of the XX – early XXI Century”. Kharkiv: Maidan, 2020. 370 p.